Pengaruh Pemberian Hipnotis Lima Jari Terhadap Ansietas Pada Lansia Hipertensi di Wisma Assisi Kota Sukabumi - Sinta Sintiawati; Sri Kurnia Dewi; Egi Mulyadi (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2024)
Hypertension is a chronic non-communicable disease and its incidence will continue to increase every year. This condition causes someone diagnosed with hypertension to experience anxiety. One alternative relaxation method for hypertension sufferers is five-finger hypnosis, also known as self-hypnosis, which aims to relieve anxiety by influencing the sympathetic nervous system and can reduce stress. Objective: To determine the effect of five finger hypnosis on anxiety levels in hypertensive elderly. Method: The design in this research uses a quasi-experimental approach using a one group pretest posttest design. Results: Based on the results of statistical tests using the Paired Samples Test, the resulting P value is 0.000 < 0.05, where it can be concluded that there is an influence of five finger hypnosis on anxiety levels in hypertensive elderly at PSTW Wisma Asisi in the Sukabumi City Area. Conclusion: there is an effect of five finger hypnosis on anxiety levels in hypertensive elderly at PSTW Wisma Assisi in the Sukabumi City Area. Suggestion: These results recommend the need for further research to look at the effectiveness of the five-finger hypnosis technique for anxiety in patients with hypertension with a larger sample size and using a control group as well as exploring comparisons with other therapies.